Designing new digital tools to augment human creative thinking at work: An application in elite sports coaching. Issue 3 (30th November 2022) - Maiden, Neil; Lockerbie, James; Zachos, Konstantinos; Wolf, Alex; Brown, Amanda
Abstract: Creative thinking is desirable in many professions. This article reports new research that followed a design science approach to develop and investigate a co‐creative tool called Sport Sparks in one profession – the coaching of professional football players. In response to a coach entering a text description of a coaching challenge (e.g., struggling to maintain the fitness of an athlete ) into the tool, the tool automatically generated potentially novel ideas (e.g., reducing game time and changing their nutrition ) that the coach could select and/or adapt and evolve into a simple action plan (e.g., which links nutrition to increased game time ). This Sport Sparks tool was designed to be an example of human‐centred artificial intelligence that aspires to empower humans, to deliver high levels of human control as well as automation, and empower people rather than emulate their expertise. It was engineered with rule‐based reasoning to automate the generation of potential new ideas that coaches could select and refine during interactions which provide high user control over this automation. The potential of such a co‐creative tool, and value of the guidelines, were demonstrated during the tool's evaluation by coaching practitioners at a Premier League football club. The practitioners used the tool to generate new ideas to coaching challenges, and reported evidence of different forms of creative thinking, although some also reported the need for more support for creative collaborations and solution planning. The paper ends by discussing future directions for both the Sport Sparks tool and other co‐creative AI tools.